2018
DOI: 10.1186/s12885-018-4276-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the local immune status between the primary and metastatic tumor in colorectal cancer: a retrospective study

Abstract: BackgroundThe anticancer immune response has been reported to correlate with cancer progression. Tumor-infiltrating lymphocytes (TILs), which are one of the indicators of host immunity, affect the tumor growth, metastasis and chemoresistance. Both TILs in the primary tumor and those in the metastatic tumor have been reported to be a useful predictor of the survival and therapeutic outcome. However, the correlation between the density of TILs in the primary and metastatic tumor is unclear. The aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 26 publications
3
18
0
Order By: Relevance
“…For CD8+CTC is reported that CTCs are having an antitumor effect through its capability to prohibit target cells on being exposed to tumor cell antigen/human leukocyte antigen 1 complex for which their T cell receptors are specific, leading to the destruction of tumor cells by apoptosis and this improving prognosis. Our results were concordant with results reported by Deschoolmeester et al [36], Ling et al [19], Sideras et al [37], and Shibutani et al [38], regarding the antitumoral effect of CTC as it was significantly higher in early non-metastatic tumors.…”
Section: Discussionsupporting
confidence: 93%
“…For CD8+CTC is reported that CTCs are having an antitumor effect through its capability to prohibit target cells on being exposed to tumor cell antigen/human leukocyte antigen 1 complex for which their T cell receptors are specific, leading to the destruction of tumor cells by apoptosis and this improving prognosis. Our results were concordant with results reported by Deschoolmeester et al [36], Ling et al [19], Sideras et al [37], and Shibutani et al [38], regarding the antitumoral effect of CTC as it was significantly higher in early non-metastatic tumors.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, it is reported that the immune composition of metastatic site is close to that of the primary tumor. 35 Patients with a high frequency of intratumoral IL-17A+ cells might also have high infiltration of this cell population in their metastatic sites if the disease relapsed. It could be a possible reason for how these cells contribute to the therapeutic outcome but need to be confirmed in further study.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the local immune response impacts the clinical course not only from the primary tumour but also from metastatic liver lesions [18,19]. Thus, examining the effect of the tumour microenvironment on liver metastases might provide deeper insight into the appropriate immune biomarker ratio that may provide more accurate and reliable prognostic information for CLO.…”
Section: Introductionmentioning
confidence: 99%